Optimising outcomes for complex trauma survivors: assessing the motivators, barriers and enablers for implementing trauma informed practice within a multidisciplinary health setting - Renee C. Lovell; David Greenfield; George Johnson; Kathy Eljiz; Sue Amanatidis (BMC Health Services Research, 2022)
Abstract Background Complex trauma is a significant public health issue with detrimental health, interpersonal and psychological impacts, which can impede client recovery and result in multiple representations. ‘Trauma Informed Practice’ (TIP) is an evidence-based model which ensures safe and effective services for clients and staff. This study examines health professional’s use of TIP, and the motivators, enablers and barriers to implementation in a multidisciplinary setting. Methods A mixed methods study with 24 front-line clinicians and managers within a community health setting in Australia. A purpose designed, expert validated TIP checklist was completed, followed by semi-structured focus groups. Survey data was reported using descriptive statistics. Focus group data was digitally recorded, transcribed and thematically analysed. Results Ten key factors were identified motivating, restricting or enabling TIP implementation. Seven were organisational factors including supportive and informed management, flexibility of service models, levels of service demands, resource availability, education opportunities, good client outcomes, and reporting requirements. Philosophical approach, team orientation, and vicarious trauma/stress management were three individual professional factors. Critically, alignment in two ways was necessary for successful implementation, that is: in knowledge and understanding across organisational role levels - clinician, manager and executive; and, in professional philosophy and team orientation of individual clinicians. Conclusion Providing TIP is essential for ensuring optimum client outcomes for trauma survivors and for maintaining workforce wellbeing. Although the increasing uptake to TIP is evident within the health setting, further attention is required to address the tension between service models focused on efficiently servicing whole populations and those attuned to effectively meeting the needs of high risk groups. A complex strategy to unite therapeutic and managerial goals is necessary if client, professional and organisational needs are to be effectively met.